DIGITILAIZING GROCERY WARE TECHNOLOGY AS A COMMUNITY ECONOMY DRIVER - Diky Budiman; Dina Fara Waidah; Mey Krisselni Sitompul; Asa Bintang Kapiarsa (Jurnal Ekonomi, 2022)
This study aims to dig deeper into the use of technology that can be used by grocery shop entrepreneurs using the literature study method. The results obtained from this study indicate that grocery stalls still use manual or conventional methods, in order to be able to compete in modern times, there are four things that can be done in a form of digitizing grocery stalls. The four things, included are as follows; 1). Making a grocery shop web, 2). Grocery shop application design, 3). Technology-based sales data processing, 4). Payments or transactions are made using digital wallets. Digitalization is expected to be able to increase buying and selling activities at grocery stalls, to make them more effective and efficient, so that it can boost the people's economy.